Effect of ploughing force on cutting forces in micro-cutting with a rounded-edge cutting tool - Uysal, Alper; Altan, Erhan (ELSEVIER SCIENCE BV, 2015)
In micro-and nano-machining operations, the importance of cutting edge radius attracts attention to understand the mechanics of micro-cutting operations. In addition, the cutting edge radius causes higher ploughing forces and the ploughing force has many effects on the mechanics on micro-and nano-machining such as increasing the resultant force and making difficult the cutting. In this study, the previously developed slip-line model for orthogonal machining with a rounded-edge cutting tool was used to determine the effect of the ploughing force on the cutting and thrust forces in micro-cutting. The cutting and thrust forces were experimentally obtained and the ploughing force was calculated from the model. The effect of the ploughing force upon cutting and thrust forces was determined. This effect was higher on thrust force and increased when cutting edge radius, uncut chip thickness, cutting speed, and rake angle increased. (C) 2015 Published by Elsevier Ltd. Selection and peer-review under responsibility of TEMA - Centre for Mechanical Technology and Automation.
Keywords: Ploughing force; rounded-edge cutting tool; micro-cutting; cutting force; thrust force; SLIP-LINE FIELD; SHEARING; MODEL; Materials Science